(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Background: Human papillomavirus (HPV) infection is a major public health concern and the leading cause of cervical cancer globally. Despite the availability of safe and effective vaccines, uptake in Nigeria remains suboptimal, largely due to parental perceptions, attitudes, and socio-cultural barriers. Understanding these factors is essential for designing effective interventions to improve vaccine acceptance. Objectives: This study assessed the knowledge, perceptions, attitudes, and barriers of parents toward HPV vaccination for girls aged 9-14years in Ile-Oluji/Okeigbo Local Government Area (LGA) of Ondo State, Nigeria, and examined the association between selected socio-demographic characteristics and overall attitude toward HPV vaccination. Method of Analysis: A descriptive cross-sectional survey was conducted among 200 parents using a structured questionnaire. Data were analyzed using descriptive statistics to summarize socio-demographic characteristics, knowledge, attitudes, and barriers. Chi-square tests were performed to determine associations between selected socio-demographic variables and overall parental attitudes toward HPV vaccination. Results: The mean age of respondents was 31.6 ± 6.2 years. A majority (81.0%) had heard of HPV vaccination, primarily through healthcare providers (45.7%). Knowledge of the vaccine’s role in preventing cervical cancer was high (94.3%), but misconceptions persisted. Overall, 50.5% of parents demonstrated a positive attitude toward HPV vaccination, while 49.5% expressed negative attitudes, influenced by concerns about safety (92.5%), vaccine cost (78.0%), and cultural or religious beliefs (68.5%). Chi-square analysis revealed significant associations between educational status, religion, and overall attitude toward HPV vaccination (p < 0.05). Conclusion: Despite high awareness and recognition of the benefits of HPV vaccination, nearly half of the parents surveyed held negative attitudes, reflecting persistent misconceptions, safety concerns, and socio-cultural barriers. Strengthening public health education, ensuring vaccine affordability and accessibility, and engaging community stakeholders are critical for improving parental acceptance and uptake of HPV vaccination in Nigeria.